Penguatan Usaha melalui Pelatihan Pembukuan dan Pemasaran Produk Ikan Asap di Desa Noelbaki Kabupaten Kupang - Marce Sherly Kase; Natalia Lily Babulu; Anggelina Delviana Klau (Madani : Indonesian Journal of Civil Society, 2022)
The topic of community service chosen by the community service team was sourced from initial observations made at the “Supel” Smoked Fish Home Industry (IRT) using local wisdom products from the East Nusa Tenggara (NTT) Province, namely Smoked Fish, so it needs to be preserved. This “Supel” Smoked Fish IRT will survive if it has good management in the form of financial management in accordance with accounting standards. Based on the Focus Group Discussion (FGD) conducted with IRT owners, it was found that the financial management of this IRT was not optimal, because while running the business, the "Supel" Smoked Fish IRT owner had not implemented financial records according to accounting standards, this was due to several obstacles, including: first, the owner's lack of understanding of financial records so that financial records are not carried out periodically. Second, the marketing of "Supel" Smoked Fish IRT has not been maximized using electronic media. The methods of implementing the service include Bookkeeping training and marketing counselling using electronic media. The final result of this service activity is that the owner of the "Supel" Smoked Fish IRT has an understanding of financial records that are in accordance with accounting standards which are then applied through periodic financial records, then product marketing assistance using electronic media in the form of Instagram in marketing "Supel" Smoked Fish products so that sales are achieved. Initially, only around 60% increased to 90%.